Syndromatic hepatic ductular Hypoplasia (Alagille syndrome) in a Nigerian: A Case Report (1998)
We report what, as far as we are aware, is the first documented case of Alagille syndrome which is characterised by chronic cholestasis, characteristic facies, pulmonary stenosis and defects at the vertebral arch, in a Nigerian girl who presented at the age of two days and was followed up interminently for a period or 10.5 years. The biochemical indices suggestive of choiestasis in the patient improved with age while the height and weigh remained suboptimal. The patient had two percutaneous iiver biopsies with the second biopsy being consistent with paucity of interlobular biie duet syndrome. The characteristic facia features suggestive of the Alagille syndrome and clinical and echocardiographic evidence pulmonary stenosis were first observed at the age or 58) months. This syndrome although rare, should be considered in the differential diagnosis of conjugated hyperbilirubinaemia in Nigerian children.